Finally sofosbuvir: an oral anti-HCV drug with wide performance capability - Kayali Z; Schmidt WN (Dove Medical Press, 2014)
Zeid Kayali,1 Warren N Schmidt2,3 1Division of Gastroenterology and Hepatology, University of Southern California, Los Angeles, CA, USA; 2Department of Internal Medicine and Research Service, Veterans Affairs Medical Center, Iowa City, IA, USA; 3Roy G and Lucille A Carver College of Medicine, University of Iowa, Iowa City, IA, USA Abstract: Chronic Hepatitis C virus (HCV) infection is the leading cause of advanced liver disease worldwide. The virus successfully evades host immune detection and for many years has hampered efforts to find a safe, uncomplicated, and reliable oral antiviral therapy. Initially, interferon and ribavirin therapy was the treatment standard of care, but it offered limited performance across the wide spectrum of HCV disease and was fraught with excessive and often limiting side effects. Sofosbuvir (SOF) is a potent first-in-class nucleoside inhibitor that has recently been approved for treatment of HCV. The drug has low toxicity, a high resistance barrier, and minimal drug interactions with other HCV direct-acting antiviral agents such as protease inhibitors or anti-NS5A agents. SOF is safe and can be used across different viral genotypes, disease stages, and special patient groups, such as those coinfected with human immunodeficiency virus. When used in combination with ribavirin or another direct-acting antiviral agent, SOF has revolutionized the HCV treatment spectrum and set the stage for nearly universal HCV antiviral therapy. More so than any other anti-HCV drug developed to date, SOF offers the widest applicability for all infected patients, and new regimens will be tailored to maximize performance. Keywords: Hepatitis C virus, sofosbuvir, polymerase inhibitors, interferon-free treatment